IDENTIFIKASI LALAT BUAH (Diptera : Tephritidae) PADA PERKEBUNAN CABAI MERAH(Capsicum annum L.) DI JALUR 03 DESA KEPENUHAN SEJATI KECAMATAN KEPENUHAN KABUPATEN ROKAN HULU - Maysaroh, Siti; Yolanda, Rofiza; Lubis, Riki Riharji (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Study on fruit flies species in red chili plantation jalur 03 Kepenuhan Sejati village District Kepenuhan of Rokan Hulu. This study was conducted from November to December 2014 using a survey method. The research found 4 species with a total of 202 individuals. Bactrocera species obtained are calumniata, B. caudata, B. cucurbitae and B. papayae. Fruit fly species most widely found was B. cucurbitae the total number of 199 individuals, whereas B. calumniata, B. caudata and B. papayae there is only one individual in each species, since B. cucurbitae has a host plant more than 125 plant.